Characterization of Chestnut Tannins: Bioactive Compounds and Their Impact on Lamb Health - Bogdan Cekić; Jordan Marković; Vuk Maksimović; Dragana Ružić-Muslić; Nevena Maksimović; Ivan Ćosić; Krstina Zeljić Stojiljković (Life)
The objective of the present study was to characterize the chestnut (Castanea sativa Mill.) tannin product, Farmatan Plus® (Tanin Sevnica d.d., Sevnica, Slovenia), and to subsequently examine its effects on the blood metabolic parameters of fattening lambs, particularly in relation to their health status. Thirty lambs were randomly divided into three treatment groups: a control group without added tannin and two groups that received 9.46 g of the tannin product/kg of the diet dry matter (DM) and 18.87 g of the tannin product/kg of the diet DM. Metabolic parameters such as contents of total protein, globulin, urea, and liver enzymes (AST and GGT) were measured over a trial period of 60 days to evaluate the effects of tannin supplementation. This study represents the first in-depth characterization of Farmatan Plus®, demonstrating its richness in bioactive compounds such as vescalin and castalagin. The results showed no significant adverse effects on lamb health, with all parameters remaining within normal physiological ranges (p > 0.05). These results support the safe inclusion of chestnut tannins in the diet of lambs and underline their potential as a functional feed additive that can positively influence the health and growth performance of ruminants.